Unstable trochanteric fractures treated with proximal femoral nail show functional outcomes independent of the fracture type - Bhattacharjee, Sourav; Rasheed, Ashir Abdul (International Journal of Research in Orthopaedics, 2024)
Background: The proximal femoral nail has replaced the sliding hip screw devices and gamma nails as the implant of choice for unstable trochanteric fracture (AO 31A2-A3). In our study we aimed to find a correlation between fracture type, time taken for radiographic union and their functional outcome according to Harris Hip score at 6 months after PFN fixation of such fractures. Methods: We assessed 38 patients sustaining unstable (AO 31A2-A3) trochanteric fractures. All the fractures were treated with short PFN. Functional outcome was assessed according to the HHS at sixth month follow-up. Results: No statistically significant association was found between HHS with fracture type (p=0.184) and bone union time (p=0.587). The association between bone union time and fracture type was found to be statistically significant (p=0.007). Conclusions: Functional outcome (HHS) does not depend upon the fracture type.